Pengaruh Penggunaan Video Pembelajaran Terhadap Hasil Belajar Matematika Siswa di UPTD SMP Negeri 5 Gunungsitoli - Zega, Hakiki Necis; Zega, Yulisman (Indo-MathEdu Intellectuals Journal, 2024)
One of the problems in mathematics at UPTD SMP Negeri 5 Gunungsitoli is that student learning outcomes are still low. The objectives of the study:  To find out whether there is an effect of the use of learning videos on the remaining mathematics learning outcomes at UPTD SMP Negeri 5 Gunungsitoli. This research is experimental research with a quantitative paradigm. The research was conducted at UPTD SMP Negeri 5 Gunungsitoli which consisted of two classes, namely class VIII-A as the experimental class and class VIII-B as the control class which were selected by purposive sampling. The instrument used to determine learning outcomes is in the form of a description test. Data analysis techniques consist of calculating the average learning outcomes, variance and standard deviation, normality test, homogeneity test, and hypothesis testing in the form of an independent t-test. The results showed: The average pre-test learning result for the experimental class was 49.65% belonging to the less category and the control class was 31.45% belonging to the less category while the average learning result from the final test for the experimental class was 84.00% belonging to the good category and the control class is 70.03% belonging to the sufficient category. Based on the hypothesis testing obtained t_count = 7.283 and t_table = 1.671. Because t_count > t_(table) is 7.283 > 1.671, then accept Ha and reject H0. From the research results obtained, the researchers concluded that: There is an effect of using learning videos on students' mathematics learning outcomes at UPTD SMP Negeri 5 Gunungsitoli